MOISTURE CONTENT, TEXTURE, AND SENSORY PROPERTIES OF CHICKEN SAUSAGE WITH TEMPEH FLOUR, ARROWROOT FLOUR AND CARRAGEENAN SUBSTITUTION - Saputri, Diva Eka; Afrizal, Muhammad Handan; Rokhmah, Laela Nur; Seno, Binardo Adi; Hasbullah, Umar Hafidz Asy’ari (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Sausage is a processed minced meat product with added fillers, emulsifiers, and flavor enhancers. In line with the trend of reducing low-fat consumption, many animal-based products are being partially or completely substituted with plant-based ingredients. This study aims to formulate and characterize sausages by adding tempeh flour as the main meat substitute protein and arrowroot flour as a filler with five percentage ratios (0:80; 20:60; 40:40; 60:20; 80:0) to the total dough. The study used a completely randomized design with one factor and analyzed the texture, moisture content, and sensory data using descriptive statistical methods. The results showed that the higher the tempe flour substitution, the more brittle the texture became. Conversely, the higher the arrowroot flour content, the higher the firmness value. Based on sensory tests for taste, color, and overall texture, sausages with the highest proportion of arrowroot flour were actually preferred.